The 8th habit from efectiveness to greatness - Covey, Stephen R.; Franklin Covey; Simon & Schuster Audio (Salt Lake City, Utah : Franklin Covey ; [New York] : Distributed by Simon & Schuster Audio, 2005)
Presents a comprehensive program for achieving personal and organizational excellence by developing an awareness of how perceptions and assumptions hinder success. Provides guidance in how to find one's'unique personal significance,' inspire others, and create a workplace where people feel engaged
Title from container
Lecturer: Stephen Covey
Keywords: Self-actualization (Psychology); Success; Satisfaction